Safety of tenecteplase vs. alteplase in telestroke: a large multistate experience (STAT) - Morgan Figurelle; Sandro Corti; Oleg Collins; Lan Gao; Amanda Avila; Kristie Delfino; Laurie Mayer; Theresa Sevilis (Frontiers in Neurology)
IntroductionPrompt treatment with IV thrombolytics (IVT) in acute ischemic stroke (AIS) patients is critical for improved recovery and survival. Recently, hospital systems have switched to the IVT tenecteplase (TNK) instead of the FDA-approved alteplase (tPA) for treatment. Multiple studies and meta-analyses evaluating the efficacy and safety of TNK demonstrate similar or superior outcomes when compared to tPA. TNK is not FDA-approved for treatment, which has led to hesitation in its use and increased attention on its complication profile, including the risk of intracranial hemorrhage (ICH).MethodsData from AIS consults conducted in the emergency departments of 220 facilities across 26 states, between 1 January 2022 and 31 May 2023, were extracted from the TeleCare by TeleSpecialists™ database. The encounters were reviewed for IVT candidates, door-to-needle (DTN) time, type of IVT administered, use of advanced imaging, presence of LVO, occurrence and type of complications, complication type, symptomatic ICH, and the ECASS II ICH score.ResultsA total of 2,305 TNK patients and 3,337 tPA patients were extracted. DTN times were faster (37 min vs. 42 min, p < 0.0001), and more total complications were observed in the TNK group (87 vs. 80, p = 0.0035). In non-LVO IVT patients, the TNK group had more complications (57 vs. 47, p = 0.0078), specifically ICH (48 vs. 35, p = 0.0036). No statistically significant difference in the incidence of ICH was observed between the TNK group and the tPA group (21 vs. 18, p = 0.07). In IVT patients not accepted for NIR, the TNK group had more complications (77 vs. 69, p = 0.005), specifically ICH (63 vs. 51, p = 0.0026). In IVT patients accepted for NIR, no significant differences were observed. There were no statistically significant differences in symptomatic ICH between the groups.ConclusionThe TNK group was found to have significantly more complications, including ICH, than the tPA group driven by non-LVO patients. A closer analysis of the potential for increased risk to non-LVO patients is warranted based on this large, multistate, and multi-hospital system study.